The boy in the dress - Walliams, David 1971- (HarperCollins Children's Books, 2009)
The sparkling debut children's novel from David Walliams, co-creator and co-star of the multi-award-winning Little Britain. Dennis was different. Why was he different, you ask? Well, a small clue might be in the title of this book! Charming, surprising and hilarious -- The Boy in the Dress is everything you would expect from the co-creator of Little Britain. David Walliams's beautiful first novel will touch the hearts (and funny bones) of children and adults alike.